FACTORS INFLUENCING DAM SURVIVAL RATE IN BOVINES SUBJECTED TO CAESAREAN-SECTION - DHINDSA, S S; DHALIWAL, G S; GHUMAN, S P S (The Indian Journal of Animal Reproduction, 2023)
Forty-one dystocia affected bovines subjected to caesarean were assessed to investigate the influence ofvarious factors on dam survival rate. With reference to type of suture material (chromic catgut, CC or polyglycolicacid, PGA) used for closing uterine incision either with or without infusion ofan intra-peritoneal lubricant (sodiumcarboxy methyl cellulose, SCMC, 1 % @ 14 ml/kg), the animals were divided into group la (PGA+SCMC, n=12),lb (PGA, n=10), le (CC+SCMC, n=10) and Id (CC, n=9), which respectively had survival rate of75%, 50%, 50%and 0%. Depending upon duration between occurrence of dystocia and caesarean, animals were divided intogroup Ila (36h, n=18)which had survival rate of72.7%, 41.7% and 33.3%, ·respectively. Based upon whether animals were handled or not prior to caesarean, animals were divided into groupIlla (previously handled, n=19) and group lllb (previously not handled, n=22) and their respective survival rate was36:8% and 54.5%. Based upon the cause of dystocia, animals were divided into group Iva (feto-pelvic disproportion,n=10), I Vb ( emphysemated fetus, n=9), I Ve (uterine torsion, n= 1 O) and IVd (pelvic fracture / abnormal pelvis/ fetalmonster, n=12) which had survival rate of60%, 22.2%, 50% and 50%, respectively. In summary, high survival ratewas observed in bovines in which PGAwas used along with intra-peritoneal infusion of SCMC. Also, the survivalrate was high when duration of dystocia was short, dystocia was not handled prior to caesarean and fetus was notemphysemated.
Keywords: Bovine; Caesarean section; Dam; Survival rate